U-Pb AGE OF ZIRCONS FROM PALEOPROTEROZOIC SECONDARY QUARTZITES OF THE BOLSHOI TYUTERS ISLAND AND FROM SANDY MATRIX OF EARLY RIPHEAN CONGLOMERATES OF THE GOGLAND ISLAND (GULF OF FINLAND): FEATURES OF THE PRE-RIPHEAN HIATUS IN SEDIMENTATION IN THE NORTHEAST OF THE EAST EUROPEAN PLATFORM - E. N. Terekhov; N. B. Kuznetsov; T. V. Romanyuk; M. A. Matveev; A. B. Makeev; A. S. Novikova; M. Yu. Gushchina; A. S. Dubenskiy; V. S. Sheshukov; A. A. Iurmanov (Геодинамика и тектонофизика)
The paper presents the results of U-Pb isotope dating of zircons extracted from rocks of the southern part of the Baltic Shield (Early Riphean conglomerates and Paleoproterozoic secondary quartzites) and makes a comparison of these results with the ages of crystalline complexes of the East European Platform (EEP). The paper presents the study results on composition of quartzites from the Bol. Tyuters and Gogland islands. There has been discussion about tectonic and paleogeographical features in the period prior to the beginning of Riphean sedimentation in the northeastern part of the EEP. It is concluded that the conglomerates are composed of erosional products of mainly Paleoproterozoic and less frequently Archean crystalline complexes. At the same time, the rocks at the base of the generalized section of Riphean deposits (Gogland group), did not contain any zircons with ages referring to 200 million years prior to the inferred time (1640–1660 Ma) of the beginning of the conglomerate sequence formation. The rocks that compose the Gogland group and their underlying Paleoproterozoic basement rocks have significant differences. We associate these differences with the existence of pre-Riphean sheet-like deposits, comprising rocks of essentially quartz composition, in the southern Baltic Shield, in the upper levels of the peneplenized Paleoproterozoic basement structure. The deposits relics are only found on the Bol. Tyuters Island; in all other places, these deposits were completely eroded or underwent significant structural and material transformations. The absence of detrital zircon grains with ages ranging from 1.87 to 1.65 Ga in the clastic rocks of the Riphean basal horizons implies no noticeable Pre-Riphean and Early Riphean orogenic movements in the northeastern part of the EEP. Tectono-magmatic reactivation in this region occurred only in the middle of the Early Riphean.